2019
DOI: 10.1089/ped.2019.1008
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body Aspiration in Infants: Role of Self-Feeding

Abstract: Background: Foreign body aspiration (FBA) is a serious life-threatening condition in childhood. ''Baby-led weaning (BLW)'' is a popular method in which the babies are encouraged to self-feed to gain oral motor abilities. The role of BLW in FBA is controversial. A retrospective study was performed to evaluate the results of FBA in infants (<1 year of age) and its relation to the feeding method. Materials and Methods: Children who underwent bronchoscopy for FBA for the past 10 years were included. Infants (<1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
1
7
0
3
Order By: Relevance
“…That is, choking risk may increase if foods included within a BLW regime are not consistent with foods considered developmentally appropriate for an infant’s oral motor skills [ 62 ]. In this regard, Özyüksel et al (2019) retrospectively examined the clinical records of 75 infants (over the past 10 years, 5–12 months) who had undergone bronchoscopy due to foreign body aspiration to show that 80% of aspiration occurred during infant self-feeding, compared with only 14% during caregiver feeding [ 63 ]. In this study, the term self-feeding was applied to infants that fully fed themselves and completed a meal without the assistance of a caregiver, which is considered to confer a BLW approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, choking risk may increase if foods included within a BLW regime are not consistent with foods considered developmentally appropriate for an infant’s oral motor skills [ 62 ]. In this regard, Özyüksel et al (2019) retrospectively examined the clinical records of 75 infants (over the past 10 years, 5–12 months) who had undergone bronchoscopy due to foreign body aspiration to show that 80% of aspiration occurred during infant self-feeding, compared with only 14% during caregiver feeding [ 63 ]. In this study, the term self-feeding was applied to infants that fully fed themselves and completed a meal without the assistance of a caregiver, which is considered to confer a BLW approach.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the term self-feeding was applied to infants that fully fed themselves and completed a meal without the assistance of a caregiver, which is considered to confer a BLW approach. While these results initially imply a greater choking risk associated with BLW, it is important to note that seeds and nuts were reported to make up the vast majority of foods aspirated by infants in both complementary feeding groups, and as such, it is important that parents and caregivers are aware of the choking risk these foods pose [ 63 ]. Further to this, given that Wright et al (2011) reported that at 6 months of age 40% ( n = 604) of infants were having some form of finger food (mainly bread, rusks, or biscuits) and by 8 months of age over 90% were having finger foods (but only 51% were having them daily), it is worth noting that in the aforementioned study by Özyüksel et al (2019), the mean age of aspiration was 9 months of age [ 40 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Turkish retrospective study of children undergoing bronchoscopy for suspected aspiration of a foreign body, of the patients in whom the food-borne foreign body was actually found, 80% were feeding themselves while only 14% were being assisted by a caregiver [74].…”
Section: Cfps and Risk Of Chokingmentioning
confidence: 99%
“…En un estudio sobre diagnóstico de aspiración de cuerpo extraño se determinó que el 80% de los casos realizaba BLW al momento del episodio, siendo importante mencionar que los alimentos que lo causaron fueron: semillas, nueces, pistachos, almendras, castañas y manzana, por lo que la asfixia podría asociarse más al desconocimiento de los alimentos a ofrecer que al método en sí 42 . Por el contrario, un estudio en Reino Unido informó que el 93,5% de los bebés nunca habían tenido un episodio de asfixia, aunque este estudio se basó en el recuerdo de las madres con niños preescolares 43 .…”
Section: Riesgosunclassified
“…Özyüksel, et al 2019 42 Transversal n = 826 -Diagnóstico de aspiración de cuerpo extraño -Tipo de AC -Alimento con el que ocurrió el episodio de asfixia El 80% de los casos realizaba BLW al momento del epísodio de asfixia.…”
Section: Tabla 2 Secciones Beneficios Y Riesgosunclassified